Surgical Management of Orbital Abscesses in Domestic Rabbits (Oryctolagus cuniculus): A report of seven cases - THOMAS, ALN; KAZAKOS, GM; PARDALI, D.; PATSIKAS, MN; KOMNENOU, A. TH. (Journal of the Hellenic Veterinary Medical Society, 2020)
A case series of seven domestic rabbits with profound exophthalmos and epiphora are presented. Appetite and physical activity of the animals were mildly or severely reduced. Clinical and detailed ophthalmic examination including intraocular pressure measurements were performed, along with radiographic and ultrasonographic examination. In all animals retrobulbar masses were diagnosed forcing the globe to protrude. Teeth malocclusion was also noticed in most of the animals. Surgical intervention under general anaesthesia, included abscess drainage, flushing and teeth removal. During surgery, samples for bacterial culture and cytology exanimation were obtained. Pasteurella multocida, Staphylococcus spp and Pseudomonas spp were isolated, while cytology confirmed the clinical diagnosis of abscess formation. Surgical management resulted in retropulsion of ocular bulbi and infection elimination. Marsupialization of the abscesses facilitated flushing and topical antibiotic application postoperatively. Animals were treated postoperatively with antibiotics for at least one month, analgesics, daily wound flushing by the owner and regular debridement. Six months after surgery three rabbits had no ocular symptoms while two died in the first two months post surgically, one was lost to follow up and the other died due to unrelated cause. In conclusion, treatment of retrobulbar abscesses in rabbits may be challenging and unrewarding. Surgical management of retrobulbar abscesses without enucleation is a feasible approach, permitting vision-retaining, whereas a multimodal approach consisting of a combination of surgical and medical treatment is often necessary for a successful outcome. Τhe owner should be informed for the long lasting postoperative care as well as the high percentage of relapse.